Role of Aβ in Alzheimer’s-related synaptic dysfunction - Zhang, Huiqin; Jiang, Xuefan; Ma, Lina; Wei, Wei; Li, Zehui; Chang, Surui; Wen, Jiayu; Sun, Jiahui; Li, Hao (Frontiers in Cell and Developmental Biology, 2022)
Synaptic dysfunction is closely related to Alzheimer’s disease (AD) which is also recognized as synaptic disorder. β-amyloid (Aβ) is one of the main pathogenic factors in AD, which disrupts synaptic plasticity and mediates the synaptic toxicity through different mechanisms. Aβ disrupts glutamate receptors, such as NMDA and AMPA receptors, which mediates calcium dyshomeostasis and damages synapse plasticity characterized by long-term potentiation (LTP) suppression and long-term depression (LTD) enhancement. As Aβ stimulates and Ca2+ influx, microglial cells and astrocyte can be activated and release cytokines, which reduces glutamate uptake and further impair synapse function. Besides, extracellular glutamate accumulation induced by Aβ mediates synapse toxicity resulting from reduced glutamate receptors and glutamate spillovers. Aβ also mediates synaptic dysfunction by acting on various signaling pathways and molecular targets, disrupting mitochondria and energy metabolism. In addition, Aβ overdeposition aggravates the toxic damage of hyperphosphorylated tau to synapses. Synaptic dysfunction plays a critical role in cognitive impairment of AD. The review addresses the possible mechanisms by which Aβ mediates AD-related synaptic impairment from distant perspectives.